Implementasi Gerakan Literasi Sekolah pada Sekolah Menengah Pertama di Kecamatan Binjai Utara, Kota Binjai, Sumatera Utara - Ritha Tarigan; Humaizi Humaizi; Henry Sitorus; Sismudjito Sismudjito; Bengkel Ginting; Elvri Teresia Simbolon (PERSPEKTIF, 2022)
The School Literacy Movement (GLS) which is implemented in Indonesia in accordance with the direction of the Regulation of the Minister of Education and Culture (Permendikbud) Number 23 of 2015, is not only the ability to read and write, but includes thinking and behavior skills, namely as the outcome of a comprehensive effort involving all school members, including teachers, students, parents/guardians, and the community, which are components of the educational ecosystem that relies on the role and completeness of school library facilities and infrastructure. The purpose of this study, to describe the application of GLS in Junior High Schools in North Binjai District, Binjai City, North Sumatra. Data collection was carried out following the paradigm of qualitative research, namely observation, in-depth interviews, which were complemented by a study of documentation. The data is sourced from all stakeholders including the Principal, Teachers, School Committees, Students, and Librarians. The results of the study illustrate that the implementation of GLS in junior high schools in North Binjai District still does not meet the National Education Standards (SNP), both public and private schools, so that there needs to be firmness in local government policies and stakeholder commitment to implementing GLS which results in outstanding students, have good behavior and character, have insight into knowledge and excellent learning achievements.